The Preference of Millennial in Surabaya Towards Workspace Characteristics - Juwono, Chrisna Hadi; Kwanda, Timoticin; Anastasia, Njo (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2022)
Millennial generation grows in the advance of information technology and dominates theproductive age in Surabaya City. Their capability in operating technology makes work activities moreefficient, as a result the need for concentration in workspaces could be reduced. Previous researchfocused on millennial’s workspace, but it was limited to one workspace. Therefore, this research isconducted to find the millennial’s preferences in the type of workspace character. Data was collectedby questionnaire. Hypothesis testing using ANOVA and Kendall’s concordance test. The resultshowed that the workspace optimize concentration is less demanded. Millennial are comfortable inworkspace that collaborate with the other workers, such as team rooms, although younger millennialsneed more concentration than older millennials.